2007
DOI: 10.1094/pdis-91-9-1116
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Loss Caused by Ray Blight Disease in Tasmanian Pyrethrum Fields

Abstract: The efficacy of newly implemented fungicide recommendations on reducing the intensity of ray blight disease caused by Phoma ligulicola to achieve site-specific attainable yield potentials in Tasmanian pyrethrum fields was quantified over two seasons in 46 and 51 fields during the 2003 and 2004 growing seasons, respectively. Disease intensity and yield in two plots (10 × 24 m), one following the commercial fungicide protocol recommendations and the second receiving no fungicide, were assessed in each pyrethrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Tomato spotted wilt virus (TSWV) is also prevalent, although infected plants generally are asymptomatic (76). Ray blight is the most prevalent disease in early spring and is the primary target of spring fungicide programs (60,62,68,71,75). Sclerotinia and Botrytis flower blights can be observed when the crops are flowering from early November until harvest in December, and are managed using a fungicide program during summer flowering.…”
mentioning
confidence: 99%
“…Tomato spotted wilt virus (TSWV) is also prevalent, although infected plants generally are asymptomatic (76). Ray blight is the most prevalent disease in early spring and is the primary target of spring fungicide programs (60,62,68,71,75). Sclerotinia and Botrytis flower blights can be observed when the crops are flowering from early November until harvest in December, and are managed using a fungicide program during summer flowering.…”
mentioning
confidence: 99%
“…Results of this study identified weather and other site-specific factors that impact the risk of ray blight defoliation exceeding 40%-a level of defoliation associated with a linear increase in the loss of flowers due to ray blight (31). For the September model, the product of the number of days with rainfall ≥0.1 mm and average maximum temperature during the last 14 days was a significant predictor of ray blight severity in September.…”
Section: Discussionmentioning
confidence: 92%
“…The methodology used to assess disease intensity in fields sampled in 2003 and 2004 has been reported (31,32), and this protocol was also followed in 2005. In the current study, disease intensity assessments were made during 12 to 16 20 flowering stems were systematically selected from each of three linear transects covering the entire width of each nontreated plot (60 stems per plot in total).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations